2008
DOI: 10.1111/j.1523-5378.2008.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in Children

Abstract: The review summarizes the articles published on Helicobacter pylori in children between April 2007 and March 2008. Evidence is emerging in different populations including developing countries that the prevalence of H. pylori is declining in all age groups. The reasons for this are unclear but it is unlikely that treatment of infection or improvement in socioeconomic conditions fully explains the decline. For the first time, differences in the inflammatory response between adults and children have been well cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
1
14
0
6
Order By: Relevance
“…In the current study, the H. pylori-infected patients had a higher prevalence of lymphoid follicle formation than the uninfected patients, although the prevalence remained moderate in both groups. This finding confirms that lymphoid follicle formation is a highly specific but not sensitive indication of H. pylori infection in children (16). Kon et al also observed that the detection rate of nodular gastritis is positively associated with the pathological score of H. pylori-related gastritis (17).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the current study, the H. pylori-infected patients had a higher prevalence of lymphoid follicle formation than the uninfected patients, although the prevalence remained moderate in both groups. This finding confirms that lymphoid follicle formation is a highly specific but not sensitive indication of H. pylori infection in children (16). Kon et al also observed that the detection rate of nodular gastritis is positively associated with the pathological score of H. pylori-related gastritis (17).…”
Section: Discussionmentioning
confidence: 56%
“…This may be due to the unique immune response observed in children that resulted in limited polymorphonuclear neutrophil/monocyte infiltration of the gastric mucosa and maintained epithelial integrity (16,24). There were no patients with a normal gastric mucosa in our study.…”
Section: Discussionmentioning
confidence: 72%
“…H. pylori infection is associated with growth failure and possibly lower ghrelin levels (10). On the other hand, the likelihood of the association between H. pylori and growth failure still remains controversial (11)(12)(13)(14)(15)(16)(17). Some researchers assert that the association of H. pylori infection and growth failure is not a cause-effect relation, but rather, a coincidence of these two entities in low socioeconomic conditions (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although several articles have reported a decline in the prevalence of H. pylori infection in both children and adults over the last decade (13-14), poor socioeconomic status remains as a significant risk factor for H. pylori infection (15)(16)(17).…”
Section: Ghrelinmentioning
confidence: 99%
“…It is well known that childhood is an important period for acquisition of H. pylori infection although several recent articles have reported a decline in the prevalence of H. pylori infection in children over the last 10 years [1]. Intrafamiliar transmission of the infection, especially from mother to child, has been hypothesized as the major mode of dissemination [2].…”
Section: Helicobacter Pylorimentioning
confidence: 99%